Correlation of LMP-1 expression with KRAS and IL-8 expression in NPC WHO type III - Soehartono, Soehartono; Marini, Marini; Surjotomo, Hendradi; Fadli, Muhammad Luqman; Setijowati, Nanik (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Nasopharyngeal carcinoma (NPC) is a squamous cell carcinoma originating from mucosal epithelium of the nasopharynx with complex disease progression. About 95% are caused by Epstein-Barr virus (EBV) infection which is characterized by the detection of viral gene product protein of Latent Membrane Protein-1 (LMP-1). Tumor growth and metastasis depend on the mechanism of angiogenesis. Interleukin-8 (IL-8) is a potent angiogenic factor and involved in the angiogenesis mechanism. Kirsten Rat Sarcoma (KRAS) is one of the proto-oncogenes that has an increased expression of more than 60% in NPC. The KRAS activation played a role in the modulation of IL-8 expression by triggering several important signaling pathways, which triggered neovascularization in the process of angiogenesis. Purpose: To determine the correlation between expression of LMP-1 with KRAS and IL-8, in mechanism of angiogenesis in NPC WHO type III. Method: Analytical observational study with a cross-sectional approach involving 30 paraffin blocks of biopsy tissue from NPC patients who had not received radiotherapy or chemotherapy. Expressions of LMP-1, KRAS, and IL-8 were examined with immunohistochemistry (IHC) staining method, and calculated using manual counting by Anatomic Pathologists. Result: Statistical analysis of LMP-1 expression with KRAS showed an insignificant positive correlation (p=0.546), with a correlation coefficient (ρ=0.115). The KRAS expression with IL-8 showed an insignificant positive correlation (p=0.851), with a correlation coefficient (ρ=0.036). The LMP-1 expression with IL-8 showed a significant positive correlation (p=0.042), with a correlation coefficient (ρ=0.321). Conclusion: The increase in the expression of LMP-1 was followed with the increase in the IL-8 expression. Keywords: NPC, LMP-1, KRAS, IL-8, angiogenesis   ABSTRAK Latar belakang: Karsinoma nasofaring (KNF) adalah karsinoma sel skuamosa yang berasal dari epitel mukosa nasofaring. Perkembangannya melibatkan hubungan yang kompleks. Sekitar 95% disebabkan oleh infeksi virus Epstein-Barr (VEB) yang ditandai dengan terdeteksinya protein produk gen virus, salah satunya yaitu Latent Membrane Protein-1 (LMP-1). Pertumbuhan dan metastasis tumor tergantung pada mekanisme angiogenesis. Interleukin-8 (IL-8) adalah faktor angiogenik yang kuat, dan terlibat dalam mekanisme angiogenesis. Kirsten Rat Sarcoma (KRAS) merupakan salah satu proto- onkogen yang mengalami peningkatan ekspresi lebih dari 60% pada KNF. Aktivasi KRAS memainkan peran dalam modulasi ekspresi IL-8 dengan memicu beberapa jalur sinyal penting, dan hal ini dapat memicu neovaskularisasi pada proses angiogenesis. Tujuan: Mengetahui korelasi antara ekspresi LMP-1 dengan ekspresi KRAS dan IL-8 dalam mekanisme angiogenesis KNF WHO tipe III. Metode: Penelitian observasional analitik dengan pendekatan potong lintang yang melibatkan 30 blok parafin jaringan biopsi penderita KNF yang belum mendapat pengobatan radioterapi maupun kemoterapi. Pemeriksaan ekspresi LMP-1, KRAS, dan IL-8 menggunakan pewarnaan imunohistokimia, dan hasilnya dihitung secara manual oleh ahli Patologi Anatomi. Hasil: Analisis statistik ekspresi LMP-1 dengan KRAS menunjukkan korelasi positif yang tidak signifikan (p =0,546), dengan koefisien korelasi ρ=0,115. Ekspresi KRAS dengan IL-8 menunjukkan korelasi positif yang tidak signifikan (p=0,851), dengan koefisien korelasi ρ=0,036. Ekspresi LMP-1 dengan IL-8 menunjukkan korelasi positif yang signifikan (p=0,042), dengan koefisien korelasi ρ=0,321. Kesimpulan: Semakin tinggi ekspresi LMP-1, maka diikuti oleh tingginya ekspresi IL-8. Kata kunci: KNF, LMP-1, KRAS, IL-8, angiogenesis